Perlindungan Hukum bagi Korban Penipuan Investasi Berkedok Aset Kripto dalam Perspektif Hukum Positif Indonesia - Muhamad Analdy Asmadika Nuraiz; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of blockchain technology and the growing public interest in crypto assets have created new investment opportunities while increasing the risk of crypto investment fraud in Indonesia. This study analyzes the characteristics of crypto investment fraud, the applicable legal framework, legal protection for victims, perpetrators’ liability, and the effectiveness of existing legal instruments. The research employs a normative legal method using statutory, conceptual, and case approaches based on the Indonesian Criminal Code, the Electronic Information and Transactions Law, the Consumer Protection Law, Law Number 4 of 2023, and Financial Services Authority regulations on crypto assets. The findings indicate that the supervision of crypto assets has shifted to the Financial Services Authority as part of Digital Financial Assets. Legal protection is available through criminal, civil, and administrative remedies. However, its effectiveness remains limited by the cross-border nature of crypto assets, low public financial literacy, and insufficient coordination among enforcement and supervisory authorities.